Love and Mental Health: Couple Relationship Quality and Depressive Symptoms Among Chilean Emerging Adults - Fernandez-Tapia, A (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Given the growing significance of romantic relationships in the lives of emerging adults, investigating the role of perceived relationship quality in depressive symptoms is relevant for understanding mental health dynamics during this developmental stage. The present study examined the association between perceived quality of romantic relationship and depressive symptoms in emerging adults, as well as the moderating role of sex assigned at birth, sexual orientation, and age. A cross-sectional study was conducted using self-report measures with the participation of 556 Chilean emerging adults. The results indicate that greater perceived couple relationship quality, assessed through dimensions including dyadic trust, emotional intimacy, relationship satisfaction, and positive sexuality, was linked to lower depressive symptoms. The associations were not moderated by the combined effect of sex and sexual orientation, or age. In summary, these results emphasize the relevance of high-quality romantic relationships as a factor associated with depressive symptoms among emerging adults.